Advanced oxidation processes (AOPs) in water and wastewater treatment - Aziz, Hamidi Abdul, 1965-; Amr, Salem S. Abu, 1978- (Engineering Science Reference (an imprint of IGI Global), 2019)
"This book discusses the fundamentals of and recent advances oxidation processes for water and wastewater. It highlights the basic rule in water and wastewater management in particular discussions on the importance of adhering the water management hierarchy in the overall management systems"--